Pelatihan Pencatatan Pembukuan Sederhana Pada Pelaku UMKM di Janti, Yogyakarta - Maria Ignasia Dai Beda; Ika Wulandari (Universitas Katolik Widya Karya Malang, 2023)
Bookkeeping training for MSME actors who are still lacking education about the importance of bookkeeping. The purpose of this activity is to provide counseling and training to MSME actors, especially chicken noodle traders in Janti. The activity was carried out on June 23-27 for chicken noodle traders. The method implemented includes counseling and training. Based on the results of the evaluation results and observations that have been carried out, it is known that the perpetrators have been able to carry out financial records and carry out a simple bookkeeping and have been able to practice it. Through the knowledge and skills he has, the perpetrator begins to understand and knows how important simple recording and bookkeeping is in controlling finances, being aware of the business development that is being carried out, being right to buy a basic sale, and making it easier when going to make a loan at a bank in developing a business. being carried out and being more careful in managing finances.